Response of the Municipal Health System to Irma Hurricane. Aguada de Pasajeros, 2017 - Midalys Otero Hernández; Víctor René Navarro Machado; Pedro López González; Lazaro Caballero Núñez (Medisur)
Foundation: in response of the health system before a hurricane, municipalities and establishments have a protagonist role. Objective: to describe the Aguada de Pasajeros municipal health system at the Irma hurricane’s path across its territory. Methods: prospective cross study, in the health and service system, developed in the Aguada de Pasajeros Municipality between September the 7th and 30th, 2017. The universe was the territory total of workers and institutions, all involved in the response to Irma’s hurricane. A documentary review was included (plans, instructions from the Defense Councils, and the Minister of Health) and participating observation. Indicators of possible impact and municipal health situation. Results: a total of 88 actions by the municipal health system; 50 during the informative phase and 9 in alert. The plan for disaster reduction was totaly achieved, to which 9 new tasks were added. There were no deaths due to the hurricane nor morbidity after the event. There was maintained assistance coverage in sites of difficult access and shelters. All the institutions maintained vitality. Conclusion: the actions developed in the municipality allowed maintaining the health situation, the comprehensive care to the people who demanded medical services during the path of the natural phenomena across the territory institutional vitality.